Zr (IV) COMPLEXES OF SOME NITROGEN-OXYGEN DONOR LIGANDS (SEMICARBAZONES & SALICYLALDAZINE) (Sciences & Technology. A, exactes sciences, 2002)
Complexes containing mixed ligands of zirconium (IV) have been synthesized by the reaction of zirconium (IV) nitrate (Zr(NO3)4, 5H2O) with salicylaldazine (SAH2) and semicarbazone ligands benzaldehyde semicarbazone (BSCH), 4-methoxybenzaldehyde semicarbzone (MBSCH), 2-chlorobenzaldehyde semicrbazone (CISCH) and cinnamaldehyde semicarbazone (CinSCH) forming complexes of the type [Zr2(SAH)2(SCH)2](NO3)8 and [Zr2(SA)2 (SC)2](NO3)2 in neutral and basic medium respectively. The ligands and their complexes are characterized physico-chemically.